2017
DOI: 10.1002/2017jg003967
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Inputs From Riparian Vegetation Limit Oxidation of Physically Bound Organic Carbon Via Biochemical and Thermodynamic Processes

Abstract: In light of increasing terrestrial carbon (C) transport across aquatic boundaries, the mechanisms governing organic carbon (OC) oxidation along terrestrial‐aquatic interfaces are crucial to future climate predictions. Here we investigate the biochemistry, metabolic pathways, and thermodynamics corresponding to OC oxidation in the Columbia River corridor using ultrahigh‐resolution C characterization. We leverage natural vegetative differences to encompass variation in terrestrial C inputs. Our results suggest t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 74 publications
6
77
0
Order By: Relevance
“…While our results support previous field observations that emphasize the role of OM thermodynamics in predicting aerobic respiration 11,12 , we uniquely underscore the central role for OM thermodynamics in the metabolism of carbon-limited ecosystems using highly controlled laboratory experiments. A field study by Graham et al 11 showed that thermodynamically favorable OM was preferentially metabolized in sediments across a vegetation gradient. Similarly, Stegen et al 12 highlighted the importance of OM thermodynamics in regulating aerobic respiration within hyporheic zones.…”
Section: Thermodynamic Regulation Of Aerobic Respirationsupporting
confidence: 88%
See 3 more Smart Citations
“…While our results support previous field observations that emphasize the role of OM thermodynamics in predicting aerobic respiration 11,12 , we uniquely underscore the central role for OM thermodynamics in the metabolism of carbon-limited ecosystems using highly controlled laboratory experiments. A field study by Graham et al 11 showed that thermodynamically favorable OM was preferentially metabolized in sediments across a vegetation gradient. Similarly, Stegen et al 12 highlighted the importance of OM thermodynamics in regulating aerobic respiration within hyporheic zones.…”
Section: Thermodynamic Regulation Of Aerobic Respirationsupporting
confidence: 88%
“…This study was conducted using sediments from the Columbia River hyporheic zone within the Hanford Site 300 Area (approximately 46° 22’ 15.80”N, 119° 85 16’ 31.52”W) in eastern Washington, USA 10,11,45 . Hyporheic zone sediments were collected in April 2018 at five locations, separated by ~2 m (depth: ~30 cm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The river stage in the Columbia River is highly dynamic due to the upstream dam operations (Song et al, 2018). Geochemical and biogeochemical modeling for this system is subject to multiple uncertain factors, such as the permeability field controlled by geological formations and within-formation heterogeneity, river stage and river temperature dynamics under future climate scenarios, reaction network, and associated rates impacted by the abiotic environmental conditions as well as the microbial community that are present in the system (Graham et al, 2017;Stegen et al, 2016Stegen et al, , 2018. Therefore, sensitivity analysis is an essential step for better understanding the model system and implementing efficient strategies to reduce the uncertainty in model predictions.…”
Section: Implementation Of Groundwater Biogeochemical Reactive Transportmentioning
confidence: 99%